1
$\begingroup$

Can anyone explain how Wien's distribution law seen in Wien's original "On the Division of Energy in the Emission-Spectrum of a Black Body":

$$ \phi_\lambda = \frac{C}{\lambda^5} e^{-\frac{c}{\lambda \theta}},$$

where (using Wien's notation) $\phi_\lambda$ is the intensity, $\lambda$ is the wavelength, $C$ and $c$ are constants and $\theta$ is the temperature, becomes in Planck's "On the Law of Distribution of Energy in the Normal Spectrum" (in Planck's notation)

$$ E.d\lambda = \theta^5 \psi(\lambda \theta).d\lambda, $$

where $E$ is the energy, $\lambda$ is the wavelength and $\theta$ is the temperature.


SOLUTION: We want to show that Planck's expression $E = T^5 \psi (\lambda T)$ is equivalent to Wien's distribution law, which has a general form $E = F(\lambda)e^{-\frac{f(\lambda)}{T}}$, but which in more concrete terms (as shown by Wien) must be $E = \frac{C}{\lambda^5}e^{-\frac{c_1}{\lambda T}}$

First off, we divide the r.h.s. by $c^4$ which, unlike Planck's case where he deals further with frequency, here, in the wave-length expression, $c^4$ is nowhere to be found. We'll do the division nevertheless, for the sake of the discussion and will get

$$E = C T^5 \psi (\lambda T),$$

where $C = \frac{1}{c^4}$. Then we will multiply and divide the r.h.s. by $\lambda^5$ and will get

$$ E = \frac{C}{\lambda^5} (\lambda T)^5 \psi (\lambda T) $$

From the above we get

$$F(\lambda) = \frac{C}{\lambda^5}$$

and

$$e^{-\frac{c_1}{\lambda T}} = (\lambda T)^5 \psi (\lambda T).$$

So, the function $\psi(\lambda T)$ in \S6 of Planck's paper must be

$$\psi (\lambda T) = \frac{e^{-\frac{c_1}{\lambda T}} }{(\lambda T)^5}$$

in order for Planck's and Wien's expressions to be equivalent. The function $\psi$, however, doesn't constitute the whole exponent part, which is $(\lambda T)^5 \frac{e^{-\frac{c_1}{\lambda T}}} {(\lambda T)^5} = e^{-\frac{c_1}{\lambda T}}$, and that, indeed, makes the two expressions equivalent.

$\endgroup$
1
$\begingroup$

The two are clearly compatible, as we can take $$\psi(x) = \frac{1}{x^2}e^{-c/x}$$ which gives Wien's law in the way stated by the OP. In the original paper by Wien, the author starts from a version of the law which appears to be incompatible with the one stated by Planck: $$\phi_\lambda = F(\lambda) e^{-f(\lambda)/\theta}$$ where $\theta$ is the temperature, in accordance with the custom at the time. The original article by Planck mentions a specific reference for the formula he's using: M. Thiesen. Ver. Deutsch. Phys. Ges., 1900, 2, 66. The referenced journal can be found here. M. Thiesen fails to provide a derivation but quotes Wien, despite noting that

Die hier gegebene Formulierung des Gesetzes fehlt bei Wien

which means (translation mine):

The formula given here is not present in Wien's work

I could not find the two papers referenced by M. Thiesen. However, I managed to find this letter submitted to Nature in 1948 by E.O. Hercus ("The Proof of Wien's Law"), which is a brief review of Wien's proof of Planck's statement, which apparently involves fairly complicated considerations about light in a cylindrical cavity.

I could not find Wien's referenced paper, but I managed to find another one of the references, the book "The Electron Theory of Matter" by O. Richardson, which gives a proof at pages 339-342. The proof involves a lot of geometrical considerations about light in a cylindrical box, some experimental considerations and Stefan-Boltzmann's law.

EDIT. Perhaps it is useful to understand the historic progression. By considering spherical cavities, Wien (1893-1894) proves that $$\phi_\lambda = \theta^5 \psi(\lambda \theta)$$ Or equivalently, $$\phi_\lambda = \frac{\theta^5 \lambda^5}{\lambda^5} \psi(\lambda \theta)=\frac{1}{\lambda^5} \chi(\lambda \theta)$$ where we have defined a new function $\chi(\lambda\theta) = (\lambda\theta)^5 \psi(\lambda \theta)$. The functions $\chi$ and $\psi$ are unknown. This is emphasised by Richardson (p. 343):

It is probable that the relations (23) and (24) which involve the universal undetermined functions $\phi$ and $\chi$ of the argument $\lambda T$ are as far as we can get, from such very general considerations as have been employed above.

where the author adopts a different notation (his $\phi$ is our $\psi$ and $T$ is temperature). However it should be pointed out that this is enough to establish a very important result, Wien's displacement law. Indeed differentiating $\phi_\lambda$:

$$\frac{\partial \phi_\lambda}{\partial \lambda} = \lambda^{-6} \left[\lambda \theta \chi'(\lambda \theta) -5\chi(\lambda\theta) \right]$$

so the maximum of $\phi_\lambda$ is given by setting the thing inside square brackets to zero. The relevant thing is that this quantity only depends on the product $\lambda \theta$, so if a maximum is attained, it will be at $\lambda \theta=b$ for some $b$. This is Wien's displacement law.

Later Wien (1896) tries to get an explicit formula for the function $\chi$ (or equivalently for $\psi$). And he does this via a completely different path, which is illustrated in the paper referenced by the OP. The result he gets is more specific (he employs a number of assumptions, see the paper itself) but as mentioned at the beginning is compatible with the previous result.

$\endgroup$
  • $\begingroup$ Nature appears to have published only p.144 of Hercus' letter. Page 143 is missing. Does Richardson's book derive an expression of Wien's law containing $T^5$? $\endgroup$ – ganzewoort Dec 23 '17 at 1:38
  • $\begingroup$ Yes. He derives the formula which is the one you quoted. I don't think the proof is particularly interesting (it's very nineteenth century) but I can post an outline if you want $\endgroup$ – John Donne Dec 23 '17 at 1:55
  • $\begingroup$ Yeah, please do. Mind you, I'm not interested in the derivation per se. All I want to see is how the two formulae in the OP are equivalent to each other. If you can show that equivalence that'll be great. Thanks. $\endgroup$ – ganzewoort Dec 23 '17 at 2:47
  • $\begingroup$ OK, Richardson derives $L\left(\lambda\right) d\lambda = T^5 \phi(T\lambda)d\lambda$ and then multiplying and dividing the r.h.s. by $\lambda^5$ he gets $L\left(\lambda\right) d\lambda = \lambda^{-5} \chi(T\lambda)d\lambda$. But, then, how did $\chi(T\lambda)$ become $C e^{-\frac{c}{T\lambda}}$ given by Wien? $\endgroup$ – ganzewoort Dec 23 '17 at 15:44
  • $\begingroup$ How did $T^5$ melt into $T$? $\endgroup$ – ganzewoort Dec 23 '17 at 15:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.